Rehabilitating and renovation of AU-IBAR Office premise At Kenindia Business Park Building Museum Hill, Westands Road Nairobi, Kenya - African Union Inter-African Bureau for Animal Resources; AU-IBAR (My University, 2021)
The Government of Kenya has accommodated AU/IBAR in Maendeleo House since 1980, a period covering 25 years. The building has greatly deteriorated over the last five years a as result of poor management. The tenants have suffered from perennial water shortage, poor maintenance, poor safety standards, particularly as regards the lifts. Despite several complaints particularly about maintenance to the Management of Maendeleo House, the situation did not improve. In addition Maendeleo House has not been able to provide ample and appropriate parking for AU/IBAR Moreover the building hosts all kinds of different tenants. Another factor was that over the years, the AU/IBAR core and Project staff complement increased, resulting in demands for more space. Some departments were forced to rent space outside the building, which led to lack of team-work, and coordination, increased communication costs wastage of time. The total office space in Maendeleo House is 11,000 sq. ft while the real needs of the organization are at least 20,000 sq ft From the year 2003, lack of water and non-operational lifts became consistent. As a result of this, the host Government declined to renew the lease on a long term basis and decided to pay rent on a monthly basis till such time as AU/IBAR found alternative office accommodation. There was a general consensus that the office accommodation in the building did not befit the corporate image of a reputable diplomatic mission or organization. Moreover most of the private organizations and Government offices previously accommodated in the building opted to move out to more appropriate office environments. After several meetings with the host Government, AU/IBAR was given the green light to go ahead and identify suitable premises and then notify the Government of Kenya for necessary action and follow up.
Keywords: Pan-African Control of Epizootics (PACE)